Comparison of Indirect Immunofluorescence Assay as a Confirmatory Test to Detect Antibody to Human Immunodeficiency Virus with Line Imuune Assay and Western Blot Methods - Alam, Ahmed Nawsher; Siddiqua, Mahmuda; Tabassum, Shahina; Islam, Md Nazrul (Bangladesh Journal of Medical Microbiology, 2016)
In low prevalent countries of Human Immunodeficiency Virus (HIV) like Bangladesh, it is recommended that all HIVpositive sera tested by Enzyme Linked Immunosorbent Assay (ELISA) and/or rapid tests should be confirmed by Line Immune Assay (LIA) or Western Blot (WB) method. As these two tests are quite expensive, Indirect Immunofluorescence Assay (IFA) was evaluated as a confirmatory test and as an alternative to these two methods in the present study. A total of 92 subjects consisting of 46 HIV-antibody-positive patients and 46 controls were included in the study. All samples of sera were tested by ELISA and IFA methods, and some 34 of 46 HIV-antibody-positive samples were tested by LIA. One ELISA positive serum was found negative by both IFA and LIA. This result indicates that ELISA was 100% sensitive and 98.7% specific for detection of HIV antibody. Comparison between LIA with IFA on 34 samples, and WB with IFA on 26 samples showed 100% correlation between these methods. The study concluded that the IFA method is equal in performance as LIA and WB methods for the detection of antibody to HIV and can be used as a confirmatory test.